2013
DOI: 10.15603/2176-1019/mud.v21n2p1-11
|View full text |Cite
|
Sign up to set email alerts
|

Compartilhamento do Diagnóstico do HIV/AIDS: Um Estudo com Mulheres

Abstract: ResumoEste artigo é fruto de pesquisa empírica cujo objetivo foi conhecer como mulheres HIV-positivo vivem seu cotidiano após o diagnóstico. Intencionamos assinalar alguns dos aspectos relativos à descoberta de estar soropositivo, bem como de aspectos referentes ao compartilhamento da soropositividade. Realizou-se pesquisa qualitativa, recorrendo a entrevistas semiestruturadas com mulheres usuárias de um Centro de Testagem e Aconselhamento em DST/Aids. Com base na perspectiva da psicologia social crítica e das… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…16 Furthermore, several issues need to be demystified. It is known that HIV transmission is through direct contact with the blood, vaginal secretions, and sperm or breast milk of infected people.…”
Section: Resultsmentioning
confidence: 99%
“…16 Furthermore, several issues need to be demystified. It is known that HIV transmission is through direct contact with the blood, vaginal secretions, and sperm or breast milk of infected people.…”
Section: Resultsmentioning
confidence: 99%
“…HIV among women is a public health problem that deserves attention with regard to prevention and health promotion strategies, as well as understanding the content of the feminization of AIDS, which includes questions related to the history of the disease in women, to sociocultural relations of gender and the productions of meaning in their daily lives. 12 According to Nascimento et al (2013), the increasing number of women infected with the HIV virus involves the biological, social and cultural characteristics that are related to women's vulnerability. The idea of vulnerability in the context of AIDS is exposed by Rocha, Vieira and Lyra (2013) as a link between individual behavior, the social environment, human rights and public policies.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this same study shows that the most of women say that the love for their children is the great incentive for the struggle for their lives, and the adherence to treatments is performed by the desire to stay as long as possible with their offspring. 12,18 Some of these women relate pregnancy and the child to religiosity, because they believe they have been seen by God, because the child was born healthy, since motherhood represents for them an opportunity to live with different ideals, involved by perseverance and trust in life. 12 A study has found the relevance of religiosity and spirituality in the lives of women living with HIV as a coping strategy, as well as helping to promote life expectancy.…”
Section: Discussionmentioning
confidence: 99%